PENGELOLAAN KEUANGAN, STRATEGI PEMASARAN, DAN JIWA KEWIRAUSAHAAN UNTUK MENCAPAI KEUNGGULAN BERSAING - Juniariani, Ni Made Rai; Sanjaya, I Ketut Puja Wirya; Mariyatni, Ni Putu Sri (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2020)
This study aims to analyze the effect of financial management and marketing strategies on competitive advantage and to analyze the moderation effect of entrepreneurial spirit on the effect of marketing strategies and financial management on competitive advantage. The sample consisted of 76 MSMEs in Denpasar taken by simple random sampling. Research data were analyzed using Moderated Regression Analysis. Results showed that financial management and marketing strategies influenced competitive advantage and that entrepreneurial spirit strengthened the influence of financial management and marketing strategies on competitive advantage. Results of this study imply that to achieve a competitive advantage, MSMEs should have good financial management, marketing strategies, and high entrepreneurial spirit. Keywords: competitive advantage, entrepreneurship, financial management, marketing strategy